BALANCE BETWEEN FREEDOM OF SPEECH AND PROTECTION AGAINST DISINFORMATION IN THE DIGITAL MEDIA ERA: A COMPARATIVE ANALYSIS OF INTERNATIONAL STANDARDS AND NATIONAL PRACTICES - Fatkhullayeva , Sevarakhon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis analyzes the scientific and theoretical foundations of the interrelationship between freedom of expression and disinformation in the digital media era, as well as the need to ensure a proper balance between them. The thesis examines the role of freedom of expression in a democratic society, the modern forms of disinformation, and their impact on human rights. In addition, theoretical approaches are comparatively analyzed, and their advantages and limitations are assessed.